2022
DOI: 10.3390/ma15196975
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Compressive Strength and Compressive Stress–Strain of Basalt Fiber Reinforced High-Performance Concrete Using Classical Programming and Logistic Map Algorithm

Abstract: In this research, the authors have developed an algorithm for predicting the compressive strength and compressive stress–strain curve of Basalt Fiber High-Performance Concrete (BFHPC), which is enhanced by a classical programming algorithm and Logistic Map. For this purpose, different percentages of basalt fiber from 0.6 to 1.8 are mixed with High-Performance Concrete with high-volume contact of cement, fine and coarse aggregate. Compressive strengths and compressive stress–strain curves are applied after 7-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…With the drop weight test device with repeated blows, the number of blows to create a certain level of rupture is obtained, which is a measure of the material's energy absorption capacity. This test is performed by dropping a 4.54 kg weight from a height CONSTRUCTION MATERIALS AND PRODUCTS of 457 mm and repeated blows until certain cracking levels (first cracking and final cracking) continue [25][26][27][28]. 6 This test was carried out on concrete samples with disk dimensions of 15×16.36 cm obtained from concrete based on blast furnace slag treated at ambient temperatures of 25 and 90 °C at the age of 28 days and also based on equation (1) The impact energy absorption capacity E was calculated as…”
Section: Experiments Methodsmentioning
confidence: 99%
“…With the drop weight test device with repeated blows, the number of blows to create a certain level of rupture is obtained, which is a measure of the material's energy absorption capacity. This test is performed by dropping a 4.54 kg weight from a height CONSTRUCTION MATERIALS AND PRODUCTS of 457 mm and repeated blows until certain cracking levels (first cracking and final cracking) continue [25][26][27][28]. 6 This test was carried out on concrete samples with disk dimensions of 15×16.36 cm obtained from concrete based on blast furnace slag treated at ambient temperatures of 25 and 90 °C at the age of 28 days and also based on equation (1) The impact energy absorption capacity E was calculated as…”
Section: Experiments Methodsmentioning
confidence: 99%
“…The author (Tumadhir, 2013), introduced basalt fiber to enhance compressive strength, finding that 0.3% basalt fiber content yielded optimal results, albeit with a slight reduction in compressive strength upon fiber addition. The influence of basalt fibers extends to the mechanical and chemical properties of concrete, including compressive, tensile, and flexural strengths (Hasanzadeh et al, 2022;Hematibahar et al, 2022;. Methodology of current study.…”
Section: The Application Of Basalt Fiber In Civil Engineeringmentioning
confidence: 99%
“…But regarding slag, due to the high percentage CaO in slag (37%), this role can be important and influential. Replacing slag up to 20%, due to having large amounts of CaO and increasing the Si/Ca ratio, as well as the potential of CaO for ion geopolymerization and chain formation with this ion [34,35] leads to an increase in the compressive, tensile and bending strengths of +Ca2 Geopolymer concrete.…”
Section: Analysis Of Compressive Tensile and Flexural Strengthsmentioning
confidence: 99%
“…They concluded that R 2 was 0.98 for GPR forecasting. In another example, Hematibahar et al [35] used classical programming to predict compressive strength They used classical programming to forecast the compressive strength and compressive stress-strain of concrete. Their results show that R 2 was more than 0.97.…”
Section: Introductionmentioning
confidence: 99%